Optimization of offshore grid planning considering onshore network expansions. (January 2022) - Liu, Yang; Fu, Yang; Huang, Ling-ling; Ren, Zi-xu; Jia, Feng
Abstract: In the coming years, an extensive development of offshore wind energy will present a clear trend of clustering offshore wind farms (OWFs). Offshore grid is a novel concept proposed to address the problem of connecting OWFs and integrating large offshore wind energy into the regional onshore power system economically and reliably. Compared with traditional electrical systems in large OWFs, the connection of offshore grid demonstrates some new features. This paper presents a tri-level optimization strategy to optimize offshore grid planning while considering onshore network expansions simultaneously. The proposed strategy turns the optimization of these two complicated electrical networks into three nested optimization models: the 'Point of common coupling (PCC) optimizer', 'Offshore substation (OS) optimizer', and 'Offshore grid optimizer'. An engineering case from the East China Sea is discussed to illustrate the effectiveness of the proposed methodology. The results show that offshore grid demonstrates better overall economic efficiency and less marine corridor consumption. In addition, the proposed methodology can make the integration of large OWFs more friendly to onshore networks. Highlights: A novel methodology for optimal planning offshore wind farm (OWF) clusters electrical systems. Some new features of offshore grid integrating with onshore grid are summarized. The demand of friendly integration is incorporated into the offshore grid planning. A tri-level optimization strategy. Several case study on a real system are analyzed.